In vitro germination and growth of Vriesea incurvata Gaudich. (Bromeliaceae) (2018)
Vriesea incurvata in the natural environment shows some difficulties associated to the low seed germination capacity. Aiming to provide basis for the seedlings production, the results of the seeds germination percentage and the initial growth of V. incurvata seedlings in vitro conditions in different culture media, are reported. Completely randomized design was comprised of eight treatments and eight replications. The treatments were as culture media: MS (Murashige and Skoog); MS½; KC (Knudson); KC½; MS + activated carbon (AC); MS½ + AC; KC + AC; and KC½ + AC. The germination percentage was calculated from the division between the number of seeds with primary root extrusion by the total number of sowed seeds. The initial growth was evaluated considering the values of total fresh biomass, percentage of normal and dead seedlings, number and roots length, stem length, number of leaves and percentage of chlorotic, necrotic and dead leaves, respectively. All the cultures promoted high germination percentages ( 82.8%). In MS and MS½ medium, it was evidenced the highest percentage of normal seedlings, the highest values of fresh biomass production, stem growth and number of leaves. KC and KC½ medium also promoted highest percentages of normal seedlings and low percentages of necrotic and dead leaves. The addition of activated carbon in the culture media was unfavorable to promote the growth of seedlings. This suggests that MS and MS½ are the most suitable culture media for the production of Vriesea incurvata in vitro.